Association of air quality parameters and socio-demographic towards the human health in India using regression analysis - Stephen Chellakan; Muhammad Abrar Ul Haq; Farheen Akram; Gazi Md. Nurul Islam; Vinodh K. Natarajan (Cogent Economics & Finance, 2022)
This paper investigates the socio-economic impact of air pollution on human health in India. The data on vehicle emissions and health effects are obtained from secondary sources, and data relating to the source of fuel, type of kitchen, household income, age, education, respondents' social class, and air-related diseases were collected through a primary source. Face-to-face interviews were conducted to collect primary data from selected 300 households using a structured questionnaire in rural and urban areas in India. The study results show that the higher-income households use alternative clean fuels like Liquefied Petroleum Gas (LPG) and electricity. The results indicate that the solid fuel users who used a kitchen without a partition wall were mostly affected by air-related diseases compared to other fuel users. The regression results indicate that the age of the household head has a positive 9.3%, gender of the household head has a negative 35.5%, the social class (caste) has a positive 20%, education of the household head has a negative 11.8%, household income has a negative 62.8%, kitchen type has a positive 23.7%, type of stove has a negative 30.7%, and type of fuel has a positive 33.1% effect on air related diseases. The study concluded that there is a need to prioritize promoting income and employment opportunities for the poor rural community. The infrastructure development activities could reduce the pollution from the vehicle. Implementing environmental education programs and campaigns could reduce the health problems in rural and urban areas in India.
Keywords: 330; Indoor air pollution; outdoor air pollution; human health; CO2 emission